What Are Required Basically by Users of a Hotel Internship Programme: Hard-skills or Soft-skills? - Kunanusorn, Anusorn (Advances in Social Sciences Research Journal, 2021)
What Are Required Basically by Users of a Hotel Internship Programme: Hard-Skills or Soft-Skills? ABSTRACT This research aimed to identify the skills that internship students are required to have in the hotel industry. To achieve these objectives, this research used questionnaires and interviews to collect data from 44 tourism businesses. Interviewings and questionnaires were obtained from businesses in Bali, Indonesia and Chiang Mai, Thailand which are both tourism attraction locations. The analysis method used for this research was descriptive analysis. The results showed that soft-skills were preferred to hard-skills. The preferred soft- skills were intrapersonal skills, interpersonal skills, self-motivation skills, autonomous learning skills, time management skills, problem-solving skills, creativity skills, and adaptability skills. These soft-skills were not well acquired, so educational institutions need to design learning programmes that allow students to live with these competencies. The current collaboration needs to be reviewed to establish a common goal and benefits for both parties regarding the development of soft-skills. There would be some other languages such as Chinese, Japanese and Korean which are necessary that we did not consider in this study but very important in tourism nowadays and future. Keywords: Internship, Soft-skills, Hard-skills